Gaps at the interface between dentine and self‐adhesive resin cement in post‐endodontic restorations quantified in 3D by phase contrast‐enhanced micro‐CT. (3rd November 2019) - Soares, A. P.; Bitter, K.; Lagrange, A.; Rack, A.; Shemesh, H.; Zaslansky, P.
Abstract: Aim: To assess the extent of gaps between root dentine and titanium or fibreglass post restorations following cementation with a self‐adhesive resin cement. Methodology: Fourteen root filled maxillary central incisors restored with prefabricated posts made of Fibreglass ( n  = 7) or Titanium ( n  = 7) and cemented with RelyX Unicem 2 were imaged by rapid, high‐resolution phase contrast‐enhanced micro‐CT (PCE‐CT) in a synchrotron X‐ray imaging facility (ID19, ESRF, 34 KeV, 0.65 µm pixel resolution). Reconstructions were used to measure canal, cement and post perimeters and cross‐sectional areas and interfacial gaps at 0.1 mm increments in the root canal space, along the cervical region of the tooth. Remnants of endodontic sealer (AH Plus), when present, were also quantified. Mann–Whitney and 2‐way ANOVA tests were used to compare findings within slices and between the two post groups. Pearson correlation coefficients ( r ) were determined between the interfacial gaps and the other measured parameters. Results: Clearly detectable gaps were found in 45% (±14%) of the interfaces between dentine and cement, along the canal in the cervical area of the tooth beneath the core. The length of interfacial gaps was moderately correlated to the canal cross‐sectional area, to the canal perimeter and to the canal area filled by cement ( R  = 0.52 ~ 0.55, P  < 0.001). There was no significant difference between samples with fibreglass or titanium ( P  > 0.01). Both post types had defect‐free interfaces with cement. Endodontic sealer remnants were found on ~10% of the canal walls and were moderately correlated to the presence of gaps. Approximately 30% of the sealer‐affected interfaces exhibited no detachment between dentine, sealer and cement. Conclusions: Self‐adhesive cements had interfacial gaps along substantial regions of the root canal surface, which was not correlated with the amount of cement in the canal. PCE‐CT proved to be an excellent non‐destructive method to study root canal restorations of hydrated samples in 3D.